Peran Guru Penggerak Dalam Meningkatkan Mutu Pembelajaran Di Sekolah Dasar - Hernita; Hasanah, Enung; Zuhaery, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Primary School Leading Teacher is responsible for promoting student-centered learning, implementing innovation in learning, and improving teacher professionalism through learning communities and collaboration. This article aims to explore the role of leading teachers in enhancing the quality of learning in primary schools., including the strategies used and the problems faced when implementing them. The method in this study uses a qualitative approach, while the data sources are taken through interviews with three Leading Teachers, and school documents. Data validity testing was carried out through focus group discussions. The results of the analysis show that leading teachers play an important role in creating a more dynamic learning environment and helping students achieve their best potential. However, problems such as limited resources and disagreement from other teachers still hinder the implementation of this program. Therefore, more comprehensive support is needed to maximize the role of Leading Teachers in improving the quality of education.